Ketepatan Kodifikasi Penyebab Dasa Kematian pada Resume Medis di RSKD Duren Sawit Tahun 2022 - Rosa Patricia; Deasy Rosmala Dewi; Puteri Fannya; Daniel Happy Putra (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Coding accuracy, namely the process of conformity of the diagnosis code that has been set by the coding officer based on ICD-10 which greatly affects data reporting and administration. The basic cause of death is the course of any disease, sick condition, or injury that causes or causes the accident that causes death. The purpose of this study was to determine the accuracy of the underlying cause of death code based on the selection rule and the MMDS table in patients who died at the Duren Sawit Hospital in 2022. This study used a descriptive method with a quantitative approach which took 88 samples using a saturated sample technique by means of observation and interviews. The results of the study were obtained from 88 samples of the accuracy of the basic causeof death codes based on the general principle selection rule and rule 1 at the Duren Sawit RSKD found that 49 (56%) and 39 (44%) were incorrect. There are factors that affect the inaccuracy of using the 5M elements (Man, Money, Material, method, Machine), namely the man element because the coding officer's profession is not appropriate and less thorough and the elements of the general coding SPO method which are still being revised, do not use selection rules and MMDS tables. Suggestions that officers should be given socializationabout the selection rules and MMDS tables.